1998
DOI: 10.1159/000008555
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Mitochondrial Reduced Glutathione by S-Adenosyl-L-Methionine Administration in Ischemia-Reperfusion Injury of the Rat Steatotic Liver Induced by Choline-Methionine-Deficient Diet

Abstract: We examined whether warm ischemia-reperfusion (I/R) damage of the rat steatotic liver can be reduced by administration of S-adenosyl-L-methionine (SAMe). We examined the effect of SAMe on the mitochondrial reduced-glutathione (GSH) pool. Sixty minutes of partial left lobar vascular clamping followed by 2 h of reperfusion were employed for a model of hepatic warm ischemia. Either 5% dextrose or SAMe was injected intraperitoneally 2 h before I/R in steatotic rats (S-D5% or S-SAMe group). Serum liver enzyme conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Consistent with this outcome, previous studies reported the depletion of this pool of GSH during hepatic I/R damage, and its restoration by GSH ethyl ester [37] or SAM [38] protected steatotic livers against I/R damage. Although this concept remains to be tested in human fatty liver, mitochondrial GSH depletion has been shown in nonalcoholic steatohepatitis [39] which is associated with increased free cholesterol accumulation and StAR overexpression [40].…”
Section: Jhepat-d-10-00907-r Llacuna Et Al 18supporting
confidence: 82%
“…Consistent with this outcome, previous studies reported the depletion of this pool of GSH during hepatic I/R damage, and its restoration by GSH ethyl ester [37] or SAM [38] protected steatotic livers against I/R damage. Although this concept remains to be tested in human fatty liver, mitochondrial GSH depletion has been shown in nonalcoholic steatohepatitis [39] which is associated with increased free cholesterol accumulation and StAR overexpression [40].…”
Section: Jhepat-d-10-00907-r Llacuna Et Al 18supporting
confidence: 82%
“…16 Strategies focused on the improvement of hepatic microcirculation or the inhibition of oxygen-free radical-mediated injury have resulted in decreased injury after I/R in fatty rats livers but were insufficient to prevent hepatic injury. 15,[17][18][19][20] Multiple mechanisms are thus potentially involved in the impaired tolerance to ischemic injury of steatotic livers, and consequently, various pharmacological strategies may need to be combined to effectively protect the fatty liver. Moreover, the different mechanisms of cell death in fatty versus nonfatty livers, 21 point to the potential differences in the mechanisms involved in hepatic I/R injury in both types of the livers.…”
mentioning
confidence: 99%
“…During the period or at the end of WI, ATP was low for both steatotic and lean livers [22,43]. However, the recovery of ATP levels in post-IRI steatotic livers were slower [22,43,45], with decreased ATP [22,30,37,39,41,44,49,50] and increased ADP concentrations [27,43], and the net effect of decreased overall energy charge [43] of steatotic livers. Similarly, at the end of cold ischemia, ATP levels showed no difference between steatotic and lean livers [64].…”
Section: Bioenergetics Hepatic Energy Status (Table 6)mentioning
confidence: 99%
“…QUORUM Diagram. [18]; b, [19]; c, [20]; d, [21]; e, [22]; f, [23], g, [24]; h, [25]; i, [26]; j, [27]; k, [28]; l, [29]; m, [30]; n, [17]; o, [31]; p, [32]; q, [33]; r, [34]; s, [35]; t, [36]; u, [37] [38]; b, [39]; c, [40]; d, [41]; e, [42]; f, [43]; g, [44]; h, [45]; i, [46]; j, [47]; k, [48]; l, [49]; m, [50]; n, [51]; o, [52] [62]; c, [63]; d, [64]; e, [65]; f, [66]; g, [67]; h, [68]; i, [69]; j, [70]; k, [71]; l, [17]; m, [60]; n, [72]; o, [73]<...>…”
Section: Papers Identified From Reference Lists N=19mentioning
confidence: 99%
See 1 more Smart Citation